2013
DOI: 10.2478/pjct-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of a polymeric porous superhydrophobic thin layer on the surface of poly(vinylidenefluoride) hollow fiber membrane

Abstract: Porous superhydrophobic layer of low-density polyethylene (LDPE) was created by a simple approach on the Poly(vinylidenefl uoride) (PVDF) hollow fi ber membranes. Acetone and ethanol mixtures with different volume ratios were used as the non-solvent on the coating surface. A 5:1 (v/v) acetone/ethanol ratio provided a porous surface with a 152° ± 3.2 water contact angle. The high contact angle could reduce membrane wettability for better carbon dioxide capture when the membrane was used as gas-liquid contactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…These properties make them better alternatives for carbon capture applications. Ahmad et al (2013) deposited a superhydrophobic layer of lowdensity polyethylene (LDPE) onto poly(vinylidene fluoride) (PVDF). The material developed was porous with a 152 ± 3.2 water contact angle and maintained a higher CO 2 flux than the unamended PVDF membrane.…”
Section: Gas Membrane Contactorsmentioning
confidence: 99%
“…These properties make them better alternatives for carbon capture applications. Ahmad et al (2013) deposited a superhydrophobic layer of lowdensity polyethylene (LDPE) onto poly(vinylidene fluoride) (PVDF). The material developed was porous with a 152 ± 3.2 water contact angle and maintained a higher CO 2 flux than the unamended PVDF membrane.…”
Section: Gas Membrane Contactorsmentioning
confidence: 99%
“…A solid layer was present for all polymer coating weight concentrations, confirming the presence of a PP layer on the surface. However, there seemed to be a crack formation for 10 mg mL −1 , which could be the result of the instability of MEK with PP during the phase separation, leading to an uneven coating of the surface [38]. Tomar et al suggest that this phenomenon is possible to happen during the drying of the polymer substrate after it is coated [39].…”
Section: Pp Coating Solution Interaction With and Without The Non-solvent Pvdf Hollow Fiber Membrane Surface Morphologymentioning
confidence: 99%
“…Studies have shown that using special methods to deposit hydrophobic inorganic nanoparticles on hollow fiber membranes can obtain superhydrophobic hollow fiber membranes with strong longterm stability [11,12]. Zhang et al [13] developed a highly hydrophobic organic-inorganic composite hollow fiber membrane by incorporating a fluorinated silica inorganic (fSiO2)layer on a polyetherimide (PEI) organic membrane substrate via sol-gel process.…”
Section: Introductionmentioning
confidence: 99%